Dynamic Properties of a Sporadic Sodium Layer Revealed by Observations Over Zhongshan, Antarctica: A Case Study - Kosch, Michael J (Journal of Geophysical Research: Space Physics, 2021)
A sodium Doppler lidar system with three-directional measurements of sodium density, atmospheric wind field, and temperature was established at Zhongshan (69.4°S, 76.4°E), Antarctica. On November 14, 2019, a sporadic sodium layer (SSL) was observed at an altitude range of 93–103 km. The temporal/spatial sodium density variations of this SSL are associated with a strong sporadic E (Es) layer at nearly the same height, which is modulated by the convective electric field. By considering the structures and the time lags of the SSL's growth at three positions, the SSL appears to have a horizontal advection in an approximately westward direction with a velocity of the order of 80 m/s. This is consistent with the zonal wind velocity derived from the lidar system itself. The temporal/spatial sodium density variations strongly indicate that the formation and perturbation of SSLs are related to the evolution of ES layers due to varied electric fields and atmospheric gravity waves, while it is advected by the horizontal wind. © 2021. American Geophysical Union. All Rights Reserved.